Pengaruh Program Bpjs Kesehatan Dan Kualitas Pelayanan Terhadap Efektivitas Sistem Informasi - Siti Ulliyanti; Selfiani Selfiani (LPPM UBP, 2026)
This study was conducted to test and analyze the impact of the BPJS Kesehatan program on the health service information system at the Pasrepan Community Health Center. To test and analyze the impact of service quality on the effectiveness of the information system at the Pasrepan Community Health Center. This study utilizes primary data, with health center staff and BPJS patients as the research objects. Data were collected via questionnaires using a Likert scale technique. The study employed Google Forms distributed to 50 respondents, consisting of health center staff and BPJS patients. The researcher used multiple linear regression analysis with SPSS as the analytical tool. The results indicate that, partially, the BPJS Kesehatan program has a significant positive effect on Information System Effectiveness. Through the BPJS Kesehatan program, public access to health services has become more equitable and accessible, while also supporting more structured and efficient participant data management. Service Quality also has a significant positive partial effect on Information System Effectiveness. High-quality service can enhance patient satisfaction and facilitate the use of information systems by both staff and BPJS participants. Furthermore, the BPJS Kesehatan program and Service Quality simultaneously (together) influence the effectiveness of the Health Center's information system. The use of digital applications such as Mobile JKN has proven effective in accelerating administrative processes and improving access to information for BPJS participants; however, continuous feature enhancements and socialization are necessary for optimal utilization